Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/9176923
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Secretion and Beyond: Targeting Synapse and Neurotransmitters to Treat Neurodegenerative Diseases

Abstract: The nervous system is important, because it regulates the physiological function of the body. Neurons are the most basic structural and functional unit of the nervous system. The synapse is an asymmetric structure that is important for neuronal function. The chemical transmission mode of the synapse is realized through neurotransmitters and electrical processes. Based on vesicle transport, the abnormal information transmission process in the synapse can lead to a series of neurorelated diseases. Numerous prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 322 publications
(476 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that in clinical patients or animal models, structural degeneration, such as reduction in neurons, generally does not appear until the middle-late stage, and cognitive impairment in the early stage of the disease is more likely to be caused by abnormal synaptic function in specific brain regions (prefrontal cortex and hippocampus) [ 24 ]. In the brain, excitatory glutamatergic synapses are often made on dendritic spines that enlarge during learning.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in clinical patients or animal models, structural degeneration, such as reduction in neurons, generally does not appear until the middle-late stage, and cognitive impairment in the early stage of the disease is more likely to be caused by abnormal synaptic function in specific brain regions (prefrontal cortex and hippocampus) [ 24 ]. In the brain, excitatory glutamatergic synapses are often made on dendritic spines that enlarge during learning.…”
Section: Resultsmentioning
confidence: 99%
“…The significant down-regulation of tuba1b expression after ECoL co-treatment provided additional evidence for the protective effect of ECoL against neuronal damage in PD-like zebrafish. Besides, maintaining the structure and function of neuronal synapse is an important pathway to antagonize the onset and development of neurodegenerative disease including PD ( Wei et al, 2022 ). ECoL co-treatments might alleviate the influence of MPTP to neural synapse, as indicated by the alteration of abnormal expressions of syn2a and gap43 , which participate in neuronal differentiation and synaptogenesis, and neurite formation, respectively ( Garbarino et al, 2014 ; Hung et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when pathogenic factors affect synapses, it suppresses the brain from learning and leads to memory impairment. Currently, these synaptic changes are the targets of many pharmacological interventions [ 19 ]. All these factors result in neuronal cell death and, in some neurodegenerative disorders, can result in brain volume loss [ 14 ].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%